Innovations for Next-Generation Antibody-Drug Conjugates (Cancer Drug Discovery and Development,, 2018)
Antibody-drug conjugates (ADCs) stand at the verge of a transformation. Scores of clinical programs have yielded only a few regulatory approvals, but a wave of technological innovation now empowers us to overcome past technical challenges. This volume focuses on the next generation of ADCs and the innovations that will enable them. The book inspires the future by integrating the field's history with novel strategies and cutting-edge technologies. While the book primarily addresses ADCs for solid tumors, the last chapter explores the emerging interest in using ADCs to treat other diseases. The therapeutic rationale of ADCs is strong: to direct small molecules to the desired site of action (and away from normal tissues) by conjugation to antibodies or other targeting moieties. However, the combination of small and large molecules imposes deep complexity to lead optimization, pharmacokinetics, toxicology, analytics and manufacturing. The field has made significant advances in all of these areas by improving target selection, ADC design, manufacturing methods and clinical strategies. These innovations will inspire and educate scientists who are designing next-generation ADCs with the potential to transform the lives of patients.